Drink For You (D4U) / Aiman Nur Mad Razuki ... [et al.] - Mad Razuki, Aiman Nur; Mohd Sohaimi, Mohamad Arman Syahier; Abd Manan, Muhammad Khairuddin; Mazlan, Muhammad Zikry Hakim; Norizan, Muhammad Farhan (2022)
Drink For You offers superior drinking water to that need a fresh, clean, delicious, and cheap drinking water. Our team will ensure that everyone will be pleas with the quality of our product after purchasing our drinking water. The Partnership. Drink For You is headquartered in the City of Pasir Gudang, Johor. The partnership is owned by partners Muhammad Khairuddin Bin Abd Manan, Aiman Nur Bin Mad Razuki, Muhammad Zikry Hakim Bin Mazlan, Mohamad Arman Syahier Bin Mohd Sohaimi and Muhammad Farhan Bin Norizan. The management of Drink For You consists of every partners that will be taking hands-on management roles in the company. In addition, we have assembled a position to every partner to provide management expertise